The Branson beauty - Booth, Claire (Booth, Claire. Sheriff Hank Worth mysteries, 2016)
"The Branson Beauty, an old showboat, has crashed in the waters of an Ozark mountain lake just outside the popular tourist destination of Branson, Missouri. More than one hundred people are trapped aboard. Hank Worth is still settling into his new role as county sheriff, and when he responds to the emergency call, he knows he's in for a long winter's day of helping elderly people into rafts and bringing them ashore. He anticipates a lot of anxiety, many arguments, and extra costs for emergency equipment that will stretch the county's already thin budget to the breaking point. But those are the least of his worries after he discovers high school track star Mandy Bryson's body locked inside the Captain's private dining room"--